Biosorption of Local Textile Dyes Onto Acid-Tolerant Macro-Beads of Chitosan-Immobilized Rhizopus arrhizus Biomass - Lang, Weeranuch; Buakaew , Pitchpong; Buranaporipan, Wanvisa; Wongchawalit, Jintanart; Sakairi, Nobuo; Vanichsriratana, Wirat; Sirisansaneeyakul, Sarote (Agriculture and Natural Resources, 2013)
Industrial textile dye removal was investigated using dried fungal biomass (FB) and acid-tolerant chitosan-immobilized Rhizopus arrhizus biomass (Ch-F beads) to elucidate their potential application. The biosorption of two textile dyes, Cibacron Turquoise HGN (CT) and Remazol Red RGB (RR) was tested as dye models for phthalocyanine-based and azo-based reactive dyes. The surface charge density of Ch-F beads and FB was found to strongly accumulate both dyes under similar acidic (pH 3.0) conditions because of the synergy between the positive charges of the acidic pH and the anionic reactive dyes. The role of physicochemical properties related to their biosorption was described. Biosorption equilibrium was established within 30 min for the FB, but retarded for the Ch-F beads due to the densely packed fungal mycelia inside the beads. The diffusivity of RR and CT in the biosorbent was verified exploiting the proposed intraparticle diffusion model. According to the Langmuir model, the maximum dye uptake capacity of the Ch-F beads for RR and CT was 198.15 and 76.84 mg.g-1, respectively. The desorption of dye-loaded Ch-F was effective using 0.1 M NaOH. This indicated the desirable applicability of Ch-F beads for the treatment of wastewaters containing dyes.